Sweat loss and fluid intake during swimming training in winter and summer at an indoor swimming pool: A field study - Taimura, A.; Matsunami, M.; Sugawara, M.; Taguchi, M.; Taba, S. (1st International Scientific Conference of Aquatic Space Activities, 2008)
This study aimed to clarify weight loss and fluid intake during swimming training in winter and summer at an indoor swimming pool. The subjects were thirteen male college swimmers. The body weight before and after training, the volume and the frequency of fluid intake and urination during training were measured. Sweat loss and fluid intake during swimming training was related to pool condition. However, there was no difference in the fluid intake ratio and the frequency of fluid intake between summer and winter. Because there is considerable variability in sweat loss and fluid intake between individuals, individualized fluid replacement program are recommended during training. It is considered that swimmers should have more fluid intake before/during swimming training to prevent dehydration, especially in summer.